Natural Gas Hydrate as a Storage Mechanism for Safe, Sustainable and Economical Production from Offshore Petroleum Reserves - Michael Kezirian; S. Phoenix (Energies, 2017)
Century Fathom presents an innovative process to utilize clathrate hydrates for the production, storage and transportation of natural gas from off-shore energy reserves in deep ocean environments. The production scheme was developed by considering the preferred state of natural gas in the deep ocean and addressing the hazards associated with conventional techniques to transport natural gas. It also is designed to mitigate the significant shipping cost inherent with all methods. The resulting proposed scheme restrains transport in the hydrate form to the ocean and does not attempt to supply energy to the residential consumer. Instead; the target recipients are industrial operations. The resulting operational concept is intrinsically safer by design; environmentally sustainable and significantly cost-effective compared with currently proposed schemes for the use of natural gas hydrates and has the potential to be the optimal solution for new production of reserves; depending on the distance to shore and capacity of the petroleum reserve. A potential additional benefit is the byproduct of desalinated water.